Occlusion of the supra-aortic arterial trunks: Surgical treatment - Danza, Rómulo; Baldizán, Jorge; Olivera, Daniel; Arias, José; Galarraga, José (Cirugía del Uruguay, 1978)
In a series of 132 patients subject to carotid or subclavian- vertebral surgery, there were 4 cases of obstruction or severe stenosis of a large supraortic trunk. In all cases a revascularization procedure was employed, and the approach was cervical or cervico-axillary. An extra-anatomical dacron by-pass was employed in three cases, one o'f which was compound (subclaviansubclavian- carotidean). There was neither morbility nor mortality among these patients and symptomatology disappeared. The authors insist on the usefulness of the a cervical approach and on the possibility of revascularization regardless of etiology.